2016
DOI: 10.1016/j.jjcc.2015.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Circulating heart-type fatty acid-binding protein levels predict ventricular fibrillation in Brugada syndrome

Abstract: Evaluating myocardial damage using H-FABP may be a promising tool for predicting ventricular arrhythmia in patients with Brugada syndrome who have received ICDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Moreover, with increasing FABP3 levels, the patients had higher rates of hypertension, diabetes mellitus, abnormal QTc interval, LVSD, and all-cause mortality, and higher levels of hs-CRP, WBC count, and visfatin. These findings are consistent with current evidence that FABP3 can be considered to be a prognostic marker for arrhythmia, heart failure, AMI, and pulmonary embolism, all of which are associated with poor clinical outcomes [31,[32][33][34], and that inflammation induced by FABP3 may lead to CVD [15]. Previous studies have shown that AF and premature ventricular contractions can induce FABP3 leakage [35,36], and ventricular cell loss caused by apoptosis has been confirmed in AF tachycardiainduced cardiomyopathy [37,38].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, with increasing FABP3 levels, the patients had higher rates of hypertension, diabetes mellitus, abnormal QTc interval, LVSD, and all-cause mortality, and higher levels of hs-CRP, WBC count, and visfatin. These findings are consistent with current evidence that FABP3 can be considered to be a prognostic marker for arrhythmia, heart failure, AMI, and pulmonary embolism, all of which are associated with poor clinical outcomes [31,[32][33][34], and that inflammation induced by FABP3 may lead to CVD [15]. Previous studies have shown that AF and premature ventricular contractions can induce FABP3 leakage [35,36], and ventricular cell loss caused by apoptosis has been confirmed in AF tachycardiainduced cardiomyopathy [37,38].…”
Section: Discussionsupporting
confidence: 90%
“…Hence, AF-induced apoptosis and sympathetic nervous system activation may contribute to FABP3 leakage in patients with AF. Furthermore, FABP3 has been reported to be elevated in patients with Brugada syndrome and ventricular fibrillation despite the absence of structural heart disease and cardiac dysfunction [32]. Therefore, assessing FABP3 could provide useful information in patients with arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, this genetic disorder is defined by inherited sodium channel dysfunction with consequent risk of SCD [122]. Also in this high risk population serum H-FABP levels (>2.4 ng/mL), but not Troponin T levels, were an independent prognostic factor for appropriate ICD shocks due to VF (during a five-year follow up) indicating H-FABP as a promising biomarker for the prediction of malignant ventricular arrhythmias [93].…”
Section: Heart-type Fatty Acid Binding Protein (H-fabp)mentioning
confidence: 79%
“…It is important to identify patients at a high risk of a sudden cardiac death in order to determine the strict indication of prophylactic ICD use in clinical practice. In several previous reports, the importance of cTnT evaluation as a marker for worse prognosis has been assessed in various types of patients [17] , [18] , [19] , [20] , [21] , [22] . Sato et al demonstrated that elevation of serum cTnT levels was associated with higher mortality and myocyte degeneration in patients with idiopathic dilated cardiomyopathy [17] .…”
Section: Discussionmentioning
confidence: 99%